MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN GAMES BASED LEARNING (GBL) SISWA KELAS V UPT SD NEGERI 56 PALILANG - Febriyanti (STKIP Subang, 2025)
Improving Mathematics Learning Outcomes through the Game-Based Learning (GBL) Model for Fifth Grade Students at UPT SD Negeri 56 Palilang. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor I: Nasrun; Supervisor II: Ernawati. The main problem in this research is how to implement the Game-Based Learning model to improve students' Mathematics learning outcomes for fifth grade students at UPT SD Negeri 56 Palilang. This research aims to improve students' learning outcomes using the Game-Based Learning model for fifth grade students at UPT SD Negeri 56 Palilang. This type of research is classroom action research, consisting of two cycles where each cycle is carried out in two meetings. The research procedure includes planning, implementing actions, observation, and reflection. The subjects of this research are 16 fourth grade students at UPT SD Negeri 56 Palilang (note: there is an inconsistency mentioning fourth grade, but the main context is fifth grade). The research results show that in the first cycle, only 10 out of 16 students (63%) completed individually and met the minimum mastery criteria (KKM) or were in the sufficient category. Classically, mastery was achieved as the average score obtained was 75. In the second cycle, 14 out of 16 students (88%) met the KKM, and classical mastery was achieved with an average score of 80, which is in the good category. Additionally, the use of the game-based learning model could improve students' learning outcomes: in the pre-cycle, 0 students got very high scores; in the first cycle, this increased to 1 student; and in the second cycle, it increased to 6 students. Based on the above research results, it can be concluded that the Mathematics learning outcomes of fifth grade students at UPT SD Negeri 56 Palilang have improved through the implementation of the Game-Based Learning model.